(3CKQ GdbGfhf GdQheGfi Ydi GdTQGFY bOjegG h MOjKgG (B/ s - (3eMeO YHOGdMajX LGO YHOGdMajX jhoSas; (3eMehO YR GdYQH GdSbG (B: s ((3GdbGgQI (B: s (3eMeO YHOGdMajX LGO YHOGdMajX jhoSa (B: s, 2018)
(3JgOa GdQSGdI ai OQGSI JhVjMjI Edi EHQGR CgejI GdbGfhf GdQhneGfi h ecGfJg GdcHjQI ai GdYGde GdbOje(B: (3eQhQkG HfTCJg(B: (3h eQGMd JWhQg efP GdYUQ Gdedci Edi YUQ GdEeHQGWhQjI GdoSadi(B: (3h eUGOQg GdJi LYdJ efg bGfhf YGdei ojOQS Edi GdBf ai GdLGeYGJ GdYGdejI(B. (3h JhVM GdQSGdI CKQ GdbGfhf GdQhneGfi Ydi GdbGfhf GdeUQi GdEZQjbi(B: (3h GdCYQGa GdaQfSjI GdbOjeI(B: (3Hd h GdbGfhf GdeOfi GdaQfSi GdUGOQ ai YGe (B1804(3e Yf WQjb GddLfI GdecdaI ef fGHdjhf HJTcjdg (B.. (3HGdEVGaI ddbGfhf GdeUQi GdMOjK(B.. (3h bO YQVfG ai GdQSGdI YOe JCKjQ GdbGfhf GdQheGfi Ydi GdTQGFY GdSeGhjI(B. (3h JhUi GdQSGdI ai GdNJGe HYOg JhUjGJ efgG(B: (3EYGOI JaYjd eLdS GdYGeI eQI oCNQi Ydi CQV GdhGbY dKQGA GdMjGI GdSjGSjI h GdfghV HeUQ dMjGI CQbi hCaVd (B: (3h oJhUi CjVkG HEYGOI JaYjd hSjdI cGfJ Vef hSGFd MeGjI GdedcjI ai GdbGfhf GdQhneGfi h GdJi cGfJ JbVi HVQhQI JQc eSGaI oeYjfI Hjf GdLjQGf ai MGdI GdHfGA h ef ojNGda gPg GdbGYOI ojYQV faSg dYbhHI ERGdI GdHfGA h OaY JYhjV ddLGQ (B.. (3adh Je GdMaGX Ydi Jdc GdbGYOI GdbGfhfjI abW dcGfJ GdoWQb CcKQ EJSGYkG h Cbd EROMGekG h CLed efXQkG h Cbd EfJTGQkG ddCeQGV eeG fMof Ydjg GdBf (B.. (3h gPG eG GfJgJ Edjg GdQSGdI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe adSag GdbGfhf h JGQjNgs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdYUQ GdLeghQi s; (3GdYUQ Gdedci s; (3GdbGfhf GdQheGfi s